A pH- and Bioreducible Cationic Copolymer with Amino Acids and Piperazines for Adenovirus Delivery - Thavasyappan Thambi; Jeongmin Lee; A-Rum Yoon; Dayananda Kasala; Chae-Ok Yun (MDPI AG, 2022)
Adenoviruses (Ads) are attractive nonviral vectors and show great potential in cancer gene therapy. However, inherent properties of Ads, including immunogenicity, nonspecific toxicity, and coxsackie and adenovirus receptor (CAR)-dependent cell uptake, limit their clinical use. To surmount these issues, we developed a pH- and glutathione-responsive poly(ethylene glycol)-poly(ꞵ-aminoester)-polyethyleneimine (PPA) for conjugation with Ad. The pH sensitivity of the PPA copolymer was elegantly tuned by substitution with different amino acids (arginine, histidine, and tryptophan), piperazines (Pip1, Pip2, and Pip3), and guanidine residues in the backbone of the PPA conjugate. PPA copolymer was further functionalized with short-chain cross-linker succinimidyl 3-(2-pyridyldithio)propionate) (SPDP) to obtain PPA-SPDP for facile conjugation with Ad. The PPA-conjugated Ad (PPA-Ad) conjugate was obtained by reacting PPA-SPDP conjugate with thiolated Ad (Ad-SH). Ad-SH was prepared by reacting Ad with 2-iminothiolane. The size distribution and zeta potential results of PPA-Ad conjugate showed an increasing trend with an increase in copolymer dose. From in vitro test, it was found that the transduction efficiency of PPA-Ad conjugate in CAR-positive cells (A549 and H460 cells) was remarkably increased at the acidic pH condition (pH 6.2) when compared with PPA-Ad conjugate incubated under the physiological condition (pH 7.4). Interestingly, the increase in transduction efficiency was evidenced in CAR-negative cells (MDA-MB-231 and T24 cells). These results demonstrated that biocompatible and biodegradable PPA copolymers can efficiently cover the surface of Ad and can increase the transduction efficiency, and hence PPA copolymers can be a useful nanomaterial for viral vector delivery in cancer therapy.